Understanding prayer in the light of Ephesians 3:12-21 to experience God’s love: An ethnoscopic analysis approach - Wijaya, Hengki; Chia, Philip Suciadi; Wauran, Queency Christie (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2025)
Prayer is a spiritual bridge that connects humans with God, becoming a means for humans to express the deepest longings of their hearts. This study explores the meaning of prayer and the depth of God’s love through the lens of Ephesians 3:12-21, using an endoscopic analysis approach to uncover hidden layers of meaning. The findings are that a diverse culture of prayer colours the prayer practices of Christians, reflecting multicultural diversity and prayer can unite diversity because of the oneness of God. Prayer is a deeply personal expression of the Father, Jesus and the Holy Spirit as a unity for His people to experience the fullness of God. The implication for world missions is the role of prayer as a bridge of communication for others to bring unbelievers to God and experience the person of God. Education contributes to the spiritual growth of students and educators by enlightening the nation's life and knowing God and His will.